Behavioral adaptation to improved environmental quality: Evidence from a sanitation intervention - Lisa Cameron; An Huang; Paulo Santos; Milan Thomas (Asian Development Bank (ADB), 2024)
This paper investigates behavioral adaptation to local improvements in environmental quality. Using exogenous variation in village sanitation coverage generated by the randomized allocation of financial incentives to latrine construction in the Lao People's Democratic Republic, we find that the generalized adoption of improved sanitation led to significant reductions in the practice of boiling water for drinking. Our analysis suggests that this change is likely a behavioral response to a reduction in the health benefits associated with treating water, which decline and eventually become negligible as local adoption of improved sanitation increases. Estimates of the value of time savings associated with the reduction in water boiling suggest that this adaptation is an additional important benefit of sanitation investments, most of which likely accrues to girls and women.
Keywords: I12; O15; Q50; 330; WASH; water boiling; height-for-age; firewood collection